Micro Editing Common Error Types in Unedited Printed Articles of The Jakarta Post - Hotgantina Sinaga (Passage, 2014)
The current study, entitled Micro Editing Common Error Types in Unedited Printed Articles of The Jakarta Post investigates the types of errors and the common errors in micro editing of The Jakarta Post’s articles. The study used eight business news articles of both unedited and edited versions written by The Jakarta Post’s journalists as thedata which werecollected from October 23, 2012 to November 1, 2012. The data wereanalyzed qualitatively and the types of errors were classified based on micro editing proposed by Brooks Pinson (2013) which are grammar, usage, style, spelling and tightening. Further, the types of errors were calculated in percentage to see the common errors. The study reveals that the common errors found are grammar (174 occurrences or 58.6% of 297 occurrences of total error) which is divided into sentence problems, nouns, pronouns, verbs, modifiers, prepositions and conjunctions, then followed by errors in tightening (18.5%), errors in style (10.1%) which consist of capitalization, comma, attribution, abbreviation, hyphen and title, and then followed by errors in usage (10.1%), and spelling (2.7%). The findings indicate that the news writers have lack of proficiency in language skills.Keywords: Editing, Micro Editing, News, Newspaper, Errors